L-Cysteine-Modified Gold Nanostars for SERS-Based Copper Ions Detection in Aqueous Media - Ndokoye, P.; Ke, J.; Liu, J.; Zhao, Q.; Li, Xin Yong (American Chemical Society, 2014)
© 2014 American Chemical Society. Gold nanostars coated with cysteine (Cys-AuNSs) were successfully synthesized and used in SERS-based copper ions (Cu2+) detection in aqueous media. The strong coordination ability of cysteine (Cys) with Cu2+ and the resulting Cys-AuNSs-Cu complex formation led to AuNSs aggregation and the drastic change in intensity and strength of COOH band spectra. The aggregation of AuNSs yielded distinct SERS signals, which exhibited remarkable sensitivity and selectivity for Cu2+ over other metal ions. Using this SERS-based sensing method, we have achieved a practical detection limit of 10 µM. Such AuNSs-based detection could provide promising alternative choices for future SERS-active AuNSs application.